2018
DOI: 10.1038/mi.2017.119
|View full text |Cite
|
Sign up to set email alerts
|

Leptin receptor q223r polymorphism influences neutrophil mobilization after Clostridium difficile infection

Abstract: Clostridium difficile is the leading cause of nosocomial infections in the U.S. Clinical disease outcomes after C. difficile infection (CDI) are dependent on intensity of host inflammatory responses. Specifically, peak peripheral white blood cell (WBC) count >20×109/L is an indicator of adverse outcomes in CDI patients, and is associated with higher 30-day mortality. We show that homozygosity for a common single nucleotide polymorphism (Q to R mutation in leptin receptor that is present in up to 50% of people)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Excessive colonic tissue injury is associated with worse disease outcomes after CDI [31]. To understand the role of MIF in controlling CDI-induced damage, we assessed colonic tissue both macroscopically and microscopically.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive colonic tissue injury is associated with worse disease outcomes after CDI [31]. To understand the role of MIF in controlling CDI-induced damage, we assessed colonic tissue both macroscopically and microscopically.…”
Section: Resultsmentioning
confidence: 99%
“…In CDI, an over exuberant host inflammatory response predominated by neutrophils is typically associated with worse disease outcomes [10, 31]. We thus examined the effects of MIF neutralization on host inflammation in cecal tissue collected from mice after CDI.…”
Section: Resultsmentioning
confidence: 99%
“…However, after neutrophil extravasation into colonic lumen, CD11b binding to epithelial cells can also promote mucosal healing (Sumagin et al, 2016). We have previously observed that despite similar pathogen load or C. difficile toxin titers in QQ and RR mice, the latter group had more colonic tissue damage (Jose et al, 2018a). But, RR mice that survived the initial insult had improved histology scores and faster disease resolution later on (Jose et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that host genetic make-up impacts CDI-induced tissue neutrophilia: homozygosity for a common single nucleotide polymorphism (SNP) in leptin receptor (LEPR), rs1137101, that results in a change of amino acid at position 223 of LEPR from Glutamine [Q] to Arginine [R] ( Duggal et al, 2011 ), is also associated with an over-exuberant neutrophil response ( Jose et al, 2018a ). We found that: ( i ) prior to infection, mice with the mutant/derived LEPR allele (RR) did not exhibit any obvious differences compared to those that express the wildtype allele (QQ); ( ii ) after CDI, both groups had similar pathogen burden and toxin titers, but RR mice had more systemic and tissue neutrophils; and ( iii ) RR humans with CDI had exaggerated peripheral blood leukocytosis, compared to QQ/QR ( Jose et al, 2018a ). Thus, CDI uncovers a hyper-inflammatory phenotype in the RR host that is manifested as exaggerated blood and colonic neutrophilia.…”
Section: Introductionmentioning
confidence: 99%
“…Jose et al showed that homozygosity for leptin receptor Q223R SNP significantly increases the risk of peak peripheral WBC count >20 × 10 9 /L, which is an indicator of adverse outcomes. They have also demonstrated in a murine model of CDI, that mice homozygous for the same SNP exhibit a higher leukocyte count in blood and tissue, exaggerated tissue inflammation and higher mortality, compared with control mice [ 23 ].…”
Section: Discussionmentioning
confidence: 99%